The long noncoding RNA HOXA11‐AS promotes lung adenocarcinoma proliferation and glycolysis via the microRNA‐148b‐3p/PKM2 axis - Wenkun Chen; Xuena Li; Bulin Du; Yan Cui; Yu Ma; Yaming Li (Cancer Medicine, 2023)
Abstract Background Lung cancer is the most common malignancy in the world and a growing number of researches have focused on its metabolic characteristics. Studies have shown that the long non‐coding RNA (lncRNA) HOXA11‐AS is aberrantly expressed in many tumors. However, the role of HOXA11‐AS in lung adenocarcinoma (LUAD) glycolysis and other energy metabolism pathways has not been characterized. Method The mRNA levels of HOXA11‐AS, microRNA‐148b‐3p (miR‐148b‐3p), and pyruvate kinase M2 (PKM2) were detected using qRT‐PCR. The expression levels of proteins were measured using immunohistochemistry and western blot. The CCK‐8, EdU, and colony formation assays were used to assess proliferation. Glycolytic changes were assessed by measuring lactate production, ATP production, and 18F‐FDG uptake. Bioinformatics analysis and dual‐luciferase reporter assays were used to characterize the relationship between HOXA11‐AS, miR‐148b‐3p, and PKM2. Proliferation and glycolytic changes were analyzed in xenograft tumor experiments using Micro‐PET imaging after downregulation of HOXA11‐AS in vivo. Results The expression of HOXA11‐AS was markedly increased in LUAD, and was strongly associated with a poor prognosis. In addition, HOXA11‐AS promoted proliferation and glycolysis in LUAD, and miR‐148b‐3p inhibited proliferation and glycolysis in LUAD. Mechanistically, HOXA11‐AS positively regulated PKM2 expression by binding to miR‐148b‐3p, thereby promoting LUAD proliferation and glycolysis. In addition, HOXA11‐AS inhibited LUAD xenograft growth and glycolysis via upregulation of miR‐148b‐3p expression and downregulation of PKM2 expression in vivo. Conclusions These results showed that HOXA11‐AS enhanced LUAD proliferation and glycolysis via the miR‐148b‐3p/PKM2 axis. The findings in this paper expanded our understanding of the molecular mechanisms of LUAD tumorigenesis and glycolysis and showed that HOXA11‐AS could be useful as a diagnostic and prognostic marker for LUAD. 18F‐FDG PET/CT can be used to visually evaluate the therapeutic effect of targeting HOXA11‐AS.